How anti-PD1 treatments are changing the management of melanoma. (November 2014) - Hersey, Peter; Kakavand, Hojabr; Wilmott, James; van der Westhuizen, Andre; Gallagher, Stuart; Gowrishankar, Kavitha; Scolyer, Richard
SUMMARY : The introduction of immunotherapy based on the blockade of the PD1/PD-L1 checkpoints has been associated with high response rates and durable remissions of disease in patients with metastatic melanoma, to the extent that it is now considered the standard of care for a wide range of patients, irrespective of their BRAF or NRAS mutation status. In addition, more frequent follow-up of patients who are at high risk of recurrence after surgical treatment appears to be justified, as does neoadjuvant treatments in order to render patients treatable by surgery. The limitations of this treatment include failure of some patients to respond, a low rate of complete responses and relapses of the disease during treatment. New initiatives in order to overcome these limitations include the identification of biomarkers for the selection responders and evaluations of treatment combinations that will increase responses and their durability. The latter includes combinations with antibodies against other checkpoints on T cells and cotreatments with inhibitors of resistance pathways in melanoma.